Determinan Proses Pendidikan Terhadap Kepuasan Mahasiswa Program Studi DIII Keperawatan STIKes PHI Tahun 2013 - Herlina Herlina; Nora Haslinda (STIKes Persada Husada Indonesia, 2014)
Subsystems that make up the difference of the education system from others includes the goal, students, management, structure and schedule time, materials, teachers and practitioners, study aids, technology, facilities, quality control, research, and education costs. The purposeof this studywas to investigate determinants of the educational processto satisfy the students of STIKes Husada Persada Indonesia Diplomaof Nursing in 2013. The method used in this study was a survey that used across sectional research design. The study population are students of the Diploma of Nursing years I, II & III. Research population of 108 people. Collected data using questionnaires. Data were analyzed by univariate analysis (frequency distribution), bivariate analysis with Kais quaretest, and multivariate analysis (logistic regression test). Variables that have a significant relationship to the educational process in students’ satisfaction includes lecturers’ disciplines, delivery of content, lecturer appearance, laoratorium, libraries, educational tools, curriculum, course schedule, and administration. Results of multivariate analysis of the variables that have an influence on student satisfaction lecturers’ discipline, educationalaids, and curriculum, the dominant influence on student satisfaction is the curriculum.